Altered virulence of Highly Pathogenic Avian Influenza (HPAI) H5N8 reassortant viruses in mammalian models. Issue 1 (1st January 2018) - Park, Su-Jin; Kim, Eun-Ha; Kwon, Hyeok-Il; Song, Min-Suk; Kim, Se Mi; Kim, Young-Il; Si, Young-Jae; Lee, In-Won; Nguyen, Hiep Dinh; Shin, Ok Sarah; Kim, Chul-Joong; Choi, Young Ki
ABSTRACT: Recently identified highly pathogenic avian influenza (HPAI) H5N8 viruses (clade 2.3.4.4) are relatively low to moderately pathogenic in mammalian hosts compared with HPAI H5N1 viruses. In this study, we generated reassortant viruses comprised of A/MD/Korea/W452/2014(H5N8) with substitution of individual genes from A/EM/Korea/W149/2006(H5N1) to understand the contribution of each viral gene to virulence in mammals. Substituting the PB2 gene segment or the NA gene segment of the H5N8 virus by that from the H5N1 virus resulted in significantly enhanced pathogenicity compared with the parental H5N8 virus in mice. Of note, substitution of the PB2 gene segment of the H5N8 virus by that from the H5N1 virus resulted in a 1000-fold increase in virulence for mice compared with the parental virus (MLD50 decreased from 10 5.8 to 10 2.5 EID50 ). Further, the W452W149PB2 virus also induced the highest virus titers in lungs at all time points and the highest levels of inflammatory cytokine responses among all viruses tested. This high virulence phenotype was also confirmed by high viral titers in the respiratory tracts of infected ferrets. Further, a mini-genome assay revealed that W452W149PB2 has significantly increased polymerase activity ( p < 0.001). Taken together, our study demonstrates that a single gene substitution from other avian influenza viruses can alter the pathogenicity of recent H5N8 viruses, and therefore emphasizes the need for intensive monitoring of reassortment events among co-circulating avian and mammalian viruses.